Pelatihan Komunikasi untuk Meningkatkan Kemampuan Komunikasi Pembina Panti Asuhan - Harumi, B. Primandini Yunanda; Surjaningrum, Endang Retno; Wilani, Ni Made Ari (Jurnal Psikologi Udayana; Vol 8 No 2 (2021), 2021)
Communication is a process of delivering and receiving messages. Communication problem can arise between adults and adolescents in a foster house. This study aims to determine the effect of communication training to increase educators’ communication skill in a foster house. This study used pre-experimental design method with one group pretest-posttest design where only one group given treatment. The research sample was 7 educators who interacts with adolescents in a foster house in Bali. Measurements use observation based indikator for communication  aspects of DeVito (2016) and interview to evaluate and follow up after the communcation training ended. The training was given for 2 days. Data was analyzed using Wilcoxon signed rank test. The results show that communication training is effective to increasing communication skill of foster house’s educators.